Ten-Item Internet Gaming Disorder Test (IGDT-10): Measurement invariance and cross-cultural validation across seven language-based samples - Király, Orsolya; Bőthe, Beáta; Ramos-Diaz, Jano; Rahimi-Movaghar, Afarin; Lukavska, Katerina; Hrabec, Ondřej; Miovsky, Michal; Billieux, Joël; Deleuze, Jory; Nuyens, Filip; Karila, Laurent; Griffiths, Mark D; et al. (Psychology of addictive behaviors, 2019)
The Ten-Item Internet Gaming Disorder Test (IGDT-10) is a short screening instrument developed to assess Internet gaming disorder (IGD) as proposed in the Diagnostic and Statistical Manual of MentalDisorders, fifth edition (DSM-5), adopting a concise, clear, and consistent item-wording. According to initial studies conducted in 2014, the instrument showed promising psychometric characteristics. The present study tested the psychometric properties, including language and gender invariance, in a large international sample of online gamers. In this study, data were collected from 7,193 participants comprising Hungarian (n = 3,924), Iranian (n = 791), English-speaking (n = 754), French-speaking (n = 421), Norwegian (n = 195), Czech (n = 496), and Peruvian (n = 612) online gamers via gaming-related websites and gaming-related social-networking-site groups. A unidimensional factor structure provided a good fit to the data in all language-based samples. In addition, results indicated both language and gender invariance on the level of scalar invariance. Criterion and construct validity of the IGDT-10 was supported by its strong association with the Problematic Online Gaming Questionnaire and moderate association with weekly gaming time, psychopathological symptoms, and impulsivity. The proportions of each sample that met the cut-off score on the IGDT-10 varied between 1.61% and 4.48% in the individual samples, except for the Peruvian sample (13.44%). The IGDT-10 shows robust psychometric properties and appears suitable for conducting cross-cultural and gender comparisons across seven languages. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: dospělí; United Kingdom; Research Design; průzkumy a dotazníky; Female; Írán; Psychometrics; Korejská republika; psychometrie; srovnání kultur; návykové chování; Adult; ženské pohlaví; mladý dospělý; Kanada; Republic of Korea; Surveys and Questionnaires; Australia; Reproducibility of Results; Slovenia; Slovakia; Impulsive Behavior; lidé; Italy; Itálie; Behavior, Addictive; Spojené království; Norway; jazyk (prostředek komunikace); impulzivní chování; Norsko; faktorová analýza statistická; Austrálie; Middle Aged; Diagnostic and Statistical Manual of Mental Disorders; reprodukovatelnost výsledků; Slovinsko; Canada; Spojené státy americké; Iran; Male; Czech Republic; Diagnostický a statistický manuál mentálních poruch; Internet; videohry; Cross-Cultural Comparison; Young Adult; Video Games; United States; Language; Hungary; Česká republika; lidé středního věku; Slovenská republika; mužské pohlaví; Maďarsko; internet; Factor Analysis, Statistical; výzkumný projekt; Peru; Humans